2022
DOI: 10.3389/fpsyt.2022.824468
|View full text |Cite
|
Sign up to set email alerts
|

Positive Treatment Expectations Shape Perceived Medication Efficacy in a Translational Placebo Paradigm for the Gut-Brain Axis

Abstract: Placebo research has established the pivotal role of treatment expectations in shaping symptom experience and patient-reported treatment outcomes. Perceived treatment efficacy constitutes a relevant yet understudied aspect, especially in the context of the gut-brain axis with visceral pain as key symptom. Using a clinically relevant experimental model of visceral pain, we elucidated effects of pre-treatment expectations on post-treatment perceived treatment efficacy as an indicator of treatment satisfaction in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…Wager et al confirmed that the ex-perience of pain after thermal stimulation was reduced after convincing healthy volunteers of the analgesic effect of the substance to be applied 2 . The same was observed in a recent study by Benson et al, where expectation reduced the perception of pain in a visceral pain study 3 .…”
Section: Introductionsupporting
confidence: 87%
See 3 more Smart Citations
“…Wager et al confirmed that the ex-perience of pain after thermal stimulation was reduced after convincing healthy volunteers of the analgesic effect of the substance to be applied 2 . The same was observed in a recent study by Benson et al, where expectation reduced the perception of pain in a visceral pain study 3 .…”
Section: Introductionsupporting
confidence: 87%
“…Pain scores were different in female in comparison with male patients at VAS3r measurement. VAS3r was 3 [1][2][3][4] in women vs. 2 [1][2][3] in male patients (P=0.03). Pain scores were higher in female patients at VAS3m (5 [3][4][5] in female vs. 3 [3][4] in male patients, P=0.017), and VAS4M (4 [3][4] in female vs. 3 [2][3][4] in male patients, P=0.041).…”
Section: Table 2 Intraoperative and Postoperative Drug Consumption An...mentioning
confidence: 89%
See 2 more Smart Citations